Obesity – A global Burden, Crucial Problem for the Society - Islam, Quazi Tarikul; Reza, Ishrat Binte (Bangladesh Journal of Medicine, 2018)
Objectives: To aware doctors, patients, food producers and consumers. Data source: Online search via Google, 70 articles were down loaded, 52 valid papers were selected. Only 12 full text articles were eligible for review. Obesity rates have increased sharply over the past 30 years, creating a global public health crisis. The impact of obesity on morbidity, mortality, and health care costs is profound. Obesity and weight related complications exert a huge burden on patient suffering and social costs. In recent years, exciting advances have occurred in all 3 modalities used to treat obesity: lifestyle intervention, pharmacotherapy, and weight-loss procedures including bariatric surgery. Obese individuals lose approximately 6 to 8 kg (approximately 6% to 8% of initial weight) with 6 months of participation in a high-intensity lifestyle intervention ($ 14 treatment visits) consisting of diet, physical activity, and behavior therapy. Such losses reduce progression to type 2 diabetes in at-risk people and decrease blood pressure and triglyceride levels. All diets, regardless of macronutrient composition, can produce clinically meaningful weight loss (.5%) if they induce a deficit of 500 kcal/d. Physical activity of 150 to 180 min/week yields modest short-term weight loss compared with diet but contributes to improvements in obesity-related conditions. Gradual weight regain is common after lifestyle intervention but can be prevented by continued participation in monthly weight loss maintenance sessions, as well as by high levels of physical activity (ie, 200 to 300min/wk). Patients unable to reduce satisfactorily with lifestyle intervention may be candidates for pharmacotherapy, recommended as an adjunct. Five medications have been approved by the US Food and Drug Administration for chronic weight management, and each has its own risk/benefit profile. The addition of these medications to lifestyle intervention increases mean weight loss by 2.5 to 8.9 kg compared with placebo. Patients with severe obesity who are unable to reduce successfully with lifestyle intervention and pharmacotherapy are eligible for bariatric surgery, including Roux-en-Y gastric bypass, sleeve gastrectomy, or adjustable gastric banding. Bangladesh J Medicine Jul 2018; 29(2) : 75-83